DEFORESTASI AMAZON PADA ERA BOLSONARO (2019) - Tine Ratna Poerwantika (Indonesian Association for International Relations, 2021)
This article was written with the aim of knowing the dynamics of deforestation in Brazil, especially the Amazon forest, and to find out the driving factors for deforestation in the Amazon rainforest in 2019 from a critical perspective. The Amazon rain forest is reported to have led to massive deforestation using massive forest burning instruments in 2019, sparking reactions from various international elements. To simplify the analysis in this article, the author uses the concept of captal expansion from David Harvey and to further clarify the problem in this article the author adds the concept of deforestation from William Laurance, the writer uses descriptive analytical research methods and uses secondary data sources. In this article, the authors find various correlations between the interests of the Brazilian government and the interests of multinational companies that lead to encouragement of land clearing in various forests, especially the Amazon, on the pretext of meeting world food demand and efforts to restore Brazilian economic instability as justification.